Integration In Sustainability Management: Promoting Corporate Value In The Green Era - Firayani Firayani; Hidayani Hidayani (PT. Hafasy Dwi Nawasena, 2025)
Sustainability integration has become a strategic foundation for firms seeking to enhance corporate value in the green economy era. Increasing regulatory pressure, shifting consumer preferences toward environmentally friendly products, and the expansion of green finance have encouraged companies to embed sustainability into their operational, financial, innovation, human resource, and governance systems. This study employs a Systematic Literature Review approach to identify and synthesize empirical findings from 54 selected articles following the PRISMA procedure. The results show that sustainability integration enhances corporate value through three primary mechanisms: operational efficiency, legitimacy and reputation enhancement, and strengthened innovation capacity. Supporting factors such as green finance, green HRM, and ESG governance further reinforce this relationship, while challenges including regulatory uncertainty, internal capability gaps, and limitations in sustainability measurement may hinder integration effectiveness. The study concludes that companies that strategically and cross-functionally integrate sustainability practices tend to achieve higher market valuation and long-term business resilience. This research reinforces the view that sustainability integration is not merely a compliance obligation but a core strategic approach for building enduring corporate value.